Theoretical Approach to the Management of Epidural Hematoma (EDH): Optimal Timing for Surgical Intervention - Hafzul; Ahmad, Diwa Aulia (Talenta Universitas Sumatera Utara, 2025)
Introduction: Epidural hematoma (EDH) is a life-threatening condition that requires timely surgical intervention to prevent irreversible neurological damage, with early decompression within the